(3QSGdI GdRfGO hGdSHjd GdhGVM ddWGdH GdeQJGOs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO dehdGfG GdMGce HPGJg GdefaQO Yf eHOYGJg GdSGHb hLhOg hLhO cd TF hGdfGWb HJeLjOI cd eDef Mi s
(3BNQgG (B:s
(3EP gOGce Edi WGYJg hWGYI hdjg GdgGOi Edi eYQaJg hGdSGdc Hce efgL QMeJg hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdReGf YHOg hGdehdi MSHfG hfYe GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B38s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds